Membangun identitas nasional dalam konteks menyatukan keberagaman dalam satu bangsa - Darmawan, Muamal Hamdi (Maliki Interdisciplinary Journal, 2025)
National identity is a key element in maintaining the integrity of a nation, particularly in a country rich in diversity like Indonesia. With over 300 ethnic groups, various religions, and numerous cultures, the challenge of building an inclusive national identity becomes increasingly complex. This journal aims to explore strategies that can be implemented to unite this diversity into a strong national identity. Using a qualitative approach, this research analyzes data obtained from in-depth interviews and document studies, involving participants from diverse social, cultural, and religious backgrounds. The findings indicate that recognition of diversity is a crucial first step in constructing a national identity. Multicultural education has. Also proven effective in shaping a younger generation that appreciates differences and understands national values. Furthermore, the role of media in providing fair and diverse representation is significant in building positive perceptions among groups. Intergroup dialogue, through activities such as seminars and cultural festivals, also contributes to strengthening social relationships and reducing potential conflicts. With an integrated approach, an inclusive national identity can be created, reinforcing unity and social cohesion amidst diversity. This journal is expected to contribute to the development of ideas about national identity in Indonesia and serve as a reference for policymakers and educators in creating a harmonious and united society.